Anaerobic biodegradability of meat-processing wastes: effect of physical, chemical and enzymatic pre-treatments - Cavaleiro, A. J. (2011)
Methane is produced during the anaerobic degradation of greaves and rinds, two by-products of pig slaughter and meat-processing industry. However, although values of 914±37 and 664±35 m3 CH4 ton-1 waste (wet weight) respectively were obtained, the degradation rate in batch assays was slow and lasted between 25 and 30 days. Therefore, in order to assess the potential increase in the biodegradation rate and biodegradability of these substrates, physical (temperature), chemical (alkali) and enzymatic (lipase) pre-treatments were tested. Partial hydrolysis was achieved for all the conditions applied but the efficiency was higher in alkaline and enzymatic treatments. These conditions produced hydrolysates with higher soluble+colloidal COD, long-chain fatty acids and ammonia concentrations, comparatively with the other treatments applied. Enzymatic hydrolysis increased 14% the methane production potential of the rinds, and this increase was even higher (80%) when rinds were thermally treated before addition of the enzyme. With all other pre-treatments, anaerobic biodegradability of both wastes was not improved comparatively to the raw materials. Alkaline conditions induced a severe decreased (89%) of rinds’ biodegradability. Enzymatic pre-treatment appears to be a promising strategy for increasing methane production from meat-processing wastes.